DIBRAST: A Computer-Aided Seismic Design Procedure for Frame Structures Equipped With Hysteretic Devices - Nuzzo, Iolanda; Ciliento, Francesca; Caterino, Nicola (Frontiers in Built Environment, 2020)
This paper describes a comprehensive computer-aided seismic design approach for both new and existing frame structures equipped with hysteretic dampers. Despite continuous advancements in the state of the art demonstrating the effectiveness of these devices in mitigating seismic hazard, non-linearities involved in the problem and the articulated nature of most of the available design procedures often make them quite difficult to be implemented for real complex structures. To promote widespread use of hysteretic dampers, we present a thorough design approach that includes the application of a specific displacement-based design procedure by means of a computer-aided support tool developed in a Visual Basic environment and named DIBRAST. The software is realized to drive the designer through the dissipative system’s design. Required iterations are automated, thus significantly reducing the processing time. As its final output, it delivers the mechanical properties of the damping braces in order to meet a specific performance objective. In order to further support practitioners in the geometrical characterization of actual design dampers, authors developed an additional Visual Basic tool—the Shear Link Non-Linear Model—that is able to provide yielding force and elastic stiffness of a specific type of hysteretic device according to its geometry and material. In addition, geometric details of each device can be preliminary determined by means of newly proposed design charts, presented herein, that allow us to take into account the buckling issue too. Both developed tools are freely available online. A case study is provided to demonstrate the effectiveness of the proposed design approach and tools.